2020
DOI: 10.3390/antiox9040308
|View full text |Cite
|
Sign up to set email alerts
|

The Antioxidant Content of Coffee and Its In Vitro Activity as an Effect of Its Production Method and Roasting and Brewing Time

Abstract: Coffee is one of the most popular beverages in the world. The high production and health properties of coffee make it one of the best among daily drinks. Coffee is wrongly identified as only a stimulant because of its caffeine content. On the other hand, coffee is one of the best sources of other bioactive compounds, such as flavonoids and phenolic acids. Organic coffee is produced without artificial fertilizers and pesticides. Not only the high quality of beans but also roasting and brewing times guarantee th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 37 publications
(41 reference statements)
8
34
0
1
Order By: Relevance
“…The CAF content in Ethiopian specialty coffees is 1.5-1.6% for green beans but decreases greatly during roasting [5]. These findings for specialty coffees are consistent with recent studies suggesting that the level of CAF decreases with longer roasting times and is highest in light-and medium-roasted commercial coffees [12,41].…”
Section: Discussionsupporting
confidence: 89%
“…The CAF content in Ethiopian specialty coffees is 1.5-1.6% for green beans but decreases greatly during roasting [5]. These findings for specialty coffees are consistent with recent studies suggesting that the level of CAF decreases with longer roasting times and is highest in light-and medium-roasted commercial coffees [12,41].…”
Section: Discussionsupporting
confidence: 89%
“…A significant reduction in caffeine content of the sample coffee beans was observed during the roasting process (Eggers & Pietsch, 2001; Król et al,2019; Górecki & Hallmann, 2020). Sidama coffee incurred up to 60% reduction in its caffeine level while Harar and Yirgacheffe coffees experienced an average of 53% and 40% loss; respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Each coffee sample was roasted at light, medium, and dark degree of roast using drum roaster (BRZ 4, Probat ® , 2009), fluidized bed roaster (V3, IKAWA ® Pro, 2018), and traditional oven top roaster. The roasting temperature was set to a maximum of 200°C, and the roasting time was limited to 15 min to ensure a dark roast at the end of each roasting process (Górecki & Hallmann, 2020). Then, the roasted coffee beans were air cooled to halt exothermic reaction and allowed to stay overnight in order to allow sufficient time for full flavor development and CO 2 degassing.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, roasted beans had significantly higher antioxidant power than the green ones [ 33 ]. The results obtained by Górecki and Hallmann [ 34 ] demonstrated that coffee’s antioxidant properties are influenced by coffee origin (organic or conventional), beans roasting level and duration of infusion. Our results confirmed previous reports that Robusta has higher antioxidant properties [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%